PopZ identifies the new pole, and PodJ identifies the old pole during polar growth in Agrobacterium tumefaciens - Grangeon, Romain (Proc Natl Acad Sci U S A, 2015)
Agrobacterium tumefaciens elongates by addition of peptidoglycan (PG) only at the pole created by cell division, the growth pole, whereas the opposite pole, the old pole, is inactive for PG synthesis. How Agrobacterium assigns and maintains pole asymmetry is not understood. Here, we investigated whether polar growth is correlated with novel pole-specific localization of proteins implicated in a variety of growth and cell division pathways. The cell cycle of A. tumefaciens was monitored by time-lapse and superresolution microscopy to image the localization of A. tumefaciens homologs of proteins involved in cell division, PG synthesis and pole identity. FtsZ and FtsA accumulate at the growth pole during elongation, and improved imaging reveals FtsZ disappears from the growth pole and accumulates at the midcell before FtsA. The L,D-transpeptidase Atu0845 was detected mainly at the growth pole. A. tumefaciens specific pole-organizing protein (Pop) PopZ(At) and polar organelle development (Pod) protein PodJ(At) exhibited dynamic yet distinct behavior. PopZ(At) was found exclusively at the growing pole and quickly switches to the new growth poles of both siblings immediately after septation. PodJ(At) is initially at the old pole but then also accumulates at the growth pole as the cell cycle progresses suggesting that PodJ(At) may mediate the transition of the growth pole to an old pole. Thus, PopZ(At) is a marker for growth pole identity, whereas PodJ(At) identifies the old pole.